Effectiveness of Jatropha multifida L. Leaf Extract Gel on Incision Wound Healing in Male Mice (Mus musculus) - Rudini, Mahmud; Widiani, Nurhaida; Febriyani, Uun; Rahayu, Regita Lestari (ORGANISMS: JOURNAL OF BIOSCIENCES, 2025)
Jatropha multifida L. has been used as a traditional remedy for fresh wounds. Its bioactive compounds, including flavonoids, alkaloids, saponins, and tannins, are known for their potential to accelerate wound healing. Research on medicinal plants continues to advance in order to develop more practical pharmaceutical formulations. This study aimed to assess the effectiveness of Jatropha multifida L. leaf extract gel on incision wound healing in Mus musculus and to identify the optimal concentration. A laboratory experimental method with a Completely Randomized Design was used, consisting of five treatments: negative control (no gel), positive control (Bioplacenton), and extract gel concentrations of 15%, 30%, and 45%, each replicated three times using 15 male mice. Daily observations over 25 days included measurements of wound length, redness, scab formation and detachment, and overall wound closure. Data were analyzed using ANOVA to determine differences among treatment groups. One-way ANOVA results showed a significance value of < 0.05, indicating a meaningful effect on wound reduction. The 45% gel concentration demonstrated the highest effectiveness in promoting wound healing. This outcome is linked to the flavonoid content of Jatropha multifida, which supports vasodilation, collagen synthesis, and the strengthening of collagen fibers during the healing process.